Ecopneumastalgia: Longing for a Relationality of Spiritual Animacy within the Web of Life - Sanders, Cody J. (Journal of pastoral theology, 2025)
The article argues that most Western Christian theology lacks a sense of deep, spiritual connection with the living earth. The article theorizes a concept, ‘ecopneumastalgia,’ to describe our longing for these lost relationships with spiritually alive earth others. To make constructive theological contributions toward addressing our collective ecological crisis, Christian faith praxis must attempt to restore this inspirited connection to earth others, moving beyond simple care for the earth to a shared love – biophilia – of life that unites God, humans, and the ecological world. It calls pastoral theologians to experiment with an animistic biophilia that fosters a form of spiritual-relational healing through relational intimacy with the entire cosmic web.